(untitled) (Global Journal of Human-Social Science, 2023)
The Brazilian police are one of the ones that kill the most in the world In 2022 Brazilian police killed around 6 thousand people What does the State do in the face of this This article seeks to examine exactly that answer Based on the analysis of 37 completed court cases 2017-2018 in the city of Curitiba in the State of Paran Brazil we analyzed the police discourse on police lethality and how the judiciary interprets it The Judiciary almost always archives the case and there is no punishment Based on this information we seek to understand the relationship between police lethality and repression in the Brazilian neoliberal State the current state configuration